A simple online selective harmonic elimination pulse width modulation scheme for voltage source inverters - Salam, Zainal (Institution of Engineers Australia, 2010)
This paper proposes an online algorithm to calculate the switching angles of the selective harmonic elimination pulse-width modulation (SHE-PWM) scheme for voltage source inverters (VSIs). It is based on the quadratic curve fitting of the trajectories of the exact SHEPWM angles. The result is a generalised quadratic equation that requires only the addition and multiplication processes, allowing its implementation using a low-cost microprocessor. Changes to the number of harmonics to be eliminated and the fundamental amplitude of the pole switching waveform (NP1) can be calculated independently. This feature is particularly suitable for motor drive applications. An extensive analysis to determine the accuracy of the algorithm is carried out. It is found that the maximum difference between the exact angle and the one calculated using this scheme (defined as angle error) is less than 1° for 0 < NP1 < 0.8. For higher values of NP1 (including over-modulation), the angle error is about 8°. However, by incorporating an error correction scheme, the angle error is reduced to between 3-6 times. To verify the workability of the technique, an experimental single-phase VSI is constructed. The SHE-PWM algorithm is implemented using a fixed-point, 16-bit microprocessor. For comparison, a MATLAB simulation of the same inverter system is carried out. The result obtained from the test rig is in very close agreement with the theoretical prediction and simulation.